Factors Affecting the Efficiency and Effectiveness of Online Teaching and Learning in Higher Education - Moungprasert, Suwamarn; Pholpuntin, Sirote; Tungdamnernsawad, Supaporn; Sriboonrawd, Jiyaporn (Suan Dusit Graduate School Academic Journal, 2022)
The objective of this research was to study the structural factors affecting the efficiency and effectiveness of online teaching and learning in Higher Education. It was quantitative research methodology, the population was 6,288 undergraduate students of Suan Dusit University, academic year 2021. The sample size was determined using Taro Yamana’s formula at the statistical significance level of .05 and a total of 377 samples were derived. The opinion questionnaire with the five-point rating scale of which Cronbach’s Alpha Coefficient was 0.986 was used. The data were analyzed by descriptive statistics; mean and standard deviation, and inferential statistics; Exploratory Factor Analysis, Confirmatory Factor Analysis, and Structural Equation Modeling. The important research findings were as follows: 1) The input factors of online learning technology affected and influenced process factors, the co-effects were accounted at 77% (R2 = 0.773) with standard relative weights (Standardized Coefficients or Beta: β) of 0.120 at the statistical significance level of 0.001. The input factors of teachers and supporting staffs affected and influenced the process factors at the statistical significance level of 0.050, and the input factors of course management affected and influenced the process factors at the statistical significance level of 0.001, 2) The process factors affected and influenced the efficiency factors of online teaching and learning at the statistical significance level of 0.000, and 3) the efficiency of online teaching and learning factors affected and influenced the effectiveness of online teaching and learning factors at the statistical significance level of 0.001.